Ovário-histerectomia em cadelas por celiotomia (“técnica convencional”), miniceliotomia (“técnica do gancho”) ou por videocirurgia (via NOTES vaginal híbrida) - Souza, Fernando Wiecheteck (2011)
In veterinary videosurgery, nowadays it is been sought the development of surgical techniques widely used, such as the case of ovariohysterectomy (OHV). Theses procedures are being studied in order to provide usually a minor trauma to the tissues involved and minor physiologic alterations, reducing complications usually observed as a postoperative pain and long period of convalescence. The OHV is the most performed surgical technique in veterinary medicine due to factors such as population control and prevention of ovarian and uterine pathologies. The purpose of this study was to compare three surgical approaches for elective ovariohysterectomy in female dogs, two for open surgery (celiotomy -“conventional technique”- and mini-celiotomy -"hook technique), and a hybrid NOTES (Natural Orifice Translumenal Endoscopic Surgery). The surgeon does not have experience with NOTES and “hook” procedures. The authors considered the time of surgery, trans and postoperative complications, technical difficulties, the occurrence of postoperative pain, the amount of surgical bleeding (g) and some vital parameters: heart rate, respiratory rate, rectal temperature, invasive blood pressure and central venous pressure. The OHV by hybrid vaginal NOTES was the technique with the lowest post-surgical discomfort score and the lowest surgical bleeding, although its surgical time was higher compared to the conventional and the hook (mini-celiotomy) modalities